2021
DOI: 10.1111/1346-8138.16204
|View full text |Cite
|
Sign up to set email alerts
|

Update of recent findings in genetic hair disorders

Abstract: Genetic hair disorders, although unusual, are not very rare, and dermatologists often have opportunities to see patients. Significant advances in molecular genetics have led to identifying many causative genes for genetic hair disorders, including the recently identified causative genes, such as LSS and C3ORF52. Many patients have been detected with autosomal recessive woolly hair/hypotrichosis in the Japanese population caused by founder mutations in the LIPH gene. Additionally, many patients with genetic hai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 129 publications
(369 reference statements)
1
19
0
1
Order By: Relevance
“…1 These conditions share a number of clinical features, 1 including blister formation as found in epidermolysis bullosa simplex, 7 hyperkeratosis as exemplified by epidermolytic hyperkeratosis, 8 nail dystrophy as demonstrated in pachyonychia congenita 9 and hair abnormalities as typical of monilethrix. 10 The present observations delineate a unique phenotype combining all of the cardinal features of keratin disorders. Desmosomal disorders such as ectodermal dysplasia with skin fragility can occasionally mimic the clinical features of these conditions, most probably owing to the fact that the function of keratin filaments is in part dependent upon their ability to interact with the desmosomal plaque.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…1 These conditions share a number of clinical features, 1 including blister formation as found in epidermolysis bullosa simplex, 7 hyperkeratosis as exemplified by epidermolytic hyperkeratosis, 8 nail dystrophy as demonstrated in pachyonychia congenita 9 and hair abnormalities as typical of monilethrix. 10 The present observations delineate a unique phenotype combining all of the cardinal features of keratin disorders. Desmosomal disorders such as ectodermal dysplasia with skin fragility can occasionally mimic the clinical features of these conditions, most probably owing to the fact that the function of keratin filaments is in part dependent upon their ability to interact with the desmosomal plaque.…”
Section: Discussionmentioning
confidence: 58%
“…Keratinopathies result from pathogenic variants in genes encoding keratin proteins expressed in the skin and mucosae and their appendages 1 . These conditions share a number of clinical features, 1 including blister formation as found in epidermolysis bullosa simplex, 7 hyperkeratosis as exemplified by epidermolytic hyperkeratosis, 8 nail dystrophy as demonstrated in pachyonychia congenita 9 and hair abnormalities as typical of monilethrix 10 . The present observations delineate a unique phenotype combining all of the cardinal features of keratin disorders.…”
Section: Discussionmentioning
confidence: 61%
“…1 LIPH and other genes in which lossof-function mutations are detected in ARWH/H are involved in a signaling pathway that is critical for hair follicle development and growth. [1][2][3] The mutation c.742C > A in LIPH has been reported to be pathogenic for ARWH/H by in vitro assays. 4 A previous study reported that the mutation c.614A > G, which is highly conserved among different species (Figure 1e), led to impaired secretion of PA-PLA1α, which contributed to the development of ARWH/H.…”
Section: Letter To the Editormentioning
confidence: 99%
“…The disease is caused by mutations in LIPH, LPAR6 (also known as P2RY5), KRT25, or C3ORF52. [1][2][3] We describe a patient with ARWH/H who carried compound heterozygous mutations in the LIPH gene at c.742C > A and c.614A > G.…”
mentioning
confidence: 99%
“…Alopecia universalis is rare, but early balding may occur. Eyebrows and eyelashes are also sparse or absent [ 25 ]. The hair phenotype can be further investigated by trichoscopy and light microscopy [ 26 ].…”
Section: Phenotypementioning
confidence: 99%